"Since this is the editorial section I intend to express my opinion": Inequality and expressivity in letters to the editor. Issue 1 (2nd January 2016) - Perrin, Andrew J.
ABSTRACT: This paper analyzes the argumentative style and the characteristics of writers of newspaper letters to the editor. Writers are more likely to be White, male, older, more politically active, and less likely to be politically moderate than the local population. Inequality in political participation persists in this forum. Gender and sense of local political efficacy influence how letter writers make their points. Letters to the editor mostly display inequalities similar to other forms of political participation.